Pentingnya Nutrisi Dan Aktifitas Fisik Lansia di Posyandu Lansia “Abadi XI” Candi Baru RW 11 Desa Gonilan - Shella Dhika Rahmawati; Fitratun Najizah; Aulia Ayu Kusuma W (Sekolah Tinggi Ilmu Kesehatan Kesetiakawanan Sosial Indonesia, 2024)
Old age is a time when individuals can feel unity, integrity and reflection of their lives. If not, this will lead to inequality and can even result in pathology, a kind of mental illness (Latifah, 2010). According to Depkomindo 2010, elderly people in Indonesia in 2008 numbered 23 million people, while neglected elderly people reached 1.7 million to 2 million people. Mental health problems in the elderly can originate from 4 aspects, namely physical, psychological, social and economic. These problems can include emotional instability, irritability, easily feeling harassed, disappointed, unhappy, feelings of loss and uselessness. Elderly people with these problems are vulnerable to experiencing psychiatric disorders such as depression, anxiety (anxiety), psychosis (insanity) or drug addiction. In general, elderly mental health problems are adjustment problems. This adjustment is due to a change from the previous situation (still physically strong, working and earning) to a decline. The elderly are also identified with decreased endurance, physical activity and experiencing various kinds of diseases. The elderly will need medication, the amount or type of which depends on the disease they are suffering from. The more illnesses the elderly have, the more types of medication are needed. The large number of types of medication will cause problems, including the possibility of requiring compliance or causing confusion in using or how to take medication. Besides that, it can increase the risk of drug side effects or drug interactions. Providing good nutrition and adequate physical activity is very necessary for the elderly. This is done with the consideration that the elderly need adequate nutrition and sufficient physical activity to support and maintain health. Several factors that influence nutritional needs include: reduced ability to digest food, reduced taste, and food absorption factors.In this outreach activity for the elderly, it is hoped that the elderly in Gonilan village will benefit from what the instructors have conveyed about the importance of adequate nutrition and physical activity to maintain the health of the elderly. These include awareness in fulfilling healthy nutrition, healthy food processing, and adequate portions for the elderly